Sensor-based quality assessment system for fruits and vegetables - Kuswandi, Bambang; Siddiqui, Mohammed Wasim (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL, USA ; Abingdon, Oxon, UK : CRC Press, 2021)
"Sensor-Based Quality Assessment Systems for Fruits and Vegetables provides an abundance of valuable information on different sensing techniques for fruits and vegetables. It covers emerging technologies, such as NMR, MRI, wireless sensor networks (WSN), and radio-frequency identification (RFID) and their potential for industrial applications. Currently, a number of new sensor technologies based on electromagnetic properties have emerged, and great progress has also been made on other existing sensor technologies. These include X-ray, nuclear magnetic resonance (NMR) or magnetic resonant imaging (MRI), fluorescence, and other related developments, such as electrical impedance and permittivity (mainly microwave), thermal sensing, and selective gas/volatile sensing. These developments have opened new areas of research as well as new applications for sensing quality of fruits and vegetables. Key features of the volume: Provides an inclusive review of the developments of sensors for quality analysis and inspection of fresh fruits and vegetables. Fosters an understanding of the basic sensing techniques for quality assessment of fresh fruits and vegetables, including further technological development. Covers advanced sensing technologies, including computer vision, spectroscopy, X-rays, magnetic resonance, mechanical contact, wireless sensor networks, and radio-frequency identification sensors. Reviews the significant progress in the sensor development of noninvasive techniques for quality assessment of fruits and vegetables. Presents the current status of different sensing systems in the context of commercial application and potentials of these sensing technologies for fruits and vegetables. This volume is dedicated solely to the application of sensor technology for evaluation of quality of fruits and vegetables and will be a rich resource for professors/lecturers teaching sensor technology for food technology courses; researchers who work on sensor development, agriculture and food technology; students in related areas; and industry professionals."--
Real-Time Quality Assessment of Fruits and Vegetables: Sensing Approaches / Bambang Kuswandi -- Sensors for Ripeness Measurement of Fruits and Vegetables / Sucheta and Kartikey Chaturvedi -- Sensors for Sorting and Grading of Fruits and Vegetables / Nadia Sharif, Burera Sajid, Neelma Munir, and Shagufta Naz -- Fluorescence Tools for Sensing of Quality-Related Phytochemicals in Fruits and Vegetables / Giovanni Agati, Wolfgang Bilger, and Zoran G. Cerovic -- Electrochemical Sensors for Quality Determination of Fruits and Vegetables / Esmaeil Heydari-Bafrooei, Ali A. Ensafi, and Maryam Amini -- Electronic Nose (e-Nose) Application in the Food Industry / Swarajya Laxmi Nayak, Bindvi Arora, Shruti Sethi, and R.R. Sharma -- IR Spectroscopy for Quality of Fruits and Vegetables / Vasudha Bansal and Nitya Sharma -- Nuclear Magnetic Resonance (NMR) Spectroscopy for Quality Determination of Fruits and Vegetable / Aamir Hussain Dar, Hilal Ahmad Makroo, Shafaq Shah, and Shafat Khan -- X-Ray Imaging for Quality Detection in Fruits and Vegetables / R.R. Sharma, S. Vijay Rakesh Reddy, and G. Gajanan -- Radio Frequency Identification (RFID) / H.A. Makroo, S. Bashir, A. Jabeen, and D. Majid -- Application of Computer Vision System in Fruit Quality Monitoring / S. Bashir, A. Jabeen, H.A. Makroo, and F. Mehraj.
OCLC-licensed vendor bibliographic record.
Keywords: Fruit -- Quality; Vegetables -- Quality; Detectors; BUSINESS & ECONOMICS / Industries / Agribusiness; SCIENCE / General; SCIENCE / Life Sciences / Horticulture